FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN KALANGAN PROFESI YANG MELAKUKAN PEKERJAAN BEBAS UNTUK MEMBAYAR PAJAK - Lesmana, Desy; Panjaitan, Delfi; Maimunah, Mutiara (Jurnal Keuangan dan Bisnis, 2020)
The purpose of this study is to determine the factors that influence the willingness of the profession to pay taxes. The factors in question are knowledge of tax regulations, tax authorities and tax sanctions. This research uses empirical research type. The object of research used in this study is experts who do free work, where the samples taken are all notaries and doctors who have their own practice, in the city of Palembang. The results show that knowledge of tax regulations and tax authorities has an effect on the willingness to pay taxes in the profession. However, tax sanctions do not affect the willingness to pay taxes in the profession.